Caring Communities in Times of Crisis. Fostering a Sustainable Culture of Care - Haussmann, A. D. (Diaconia, 2024)
Aging Western societies face a growing care crisis, prompting a reevaluation of care as a collective social responsibility and driving the emergence of new care models. The concept of "caring communities" envisions care as a shared societal task, fostering mutual support and solidarity. While widely discussed in theory, empirical studies on their conditions for success and sustainability remain scarce. This qualitative, exploratory study examines church-related caring communities focused on supporting caregiving relatives. Four focus groups and nine individual interviews with stakeholders, volunteers, and caregiving relatives are analyzed using qualitative content analysis to identify key success factors and responses to crises like the pandemic. Findings highlight three core pillars essential for sustainability: structural and organizational frameworks, interpersonal and social dynamics, and a foundational culture of care. We explore how caring communities can enhance resilience by addressing these factors, while also acknowledging challenges and limitations. Our study suggests that sustainability is best achieved when communities remain adaptable, responsive to members’ needs, and foster a participatory, failure-tolerant culture.